The Star, 27 April 2007 (Star Publications (Malaysia) Berhad, 2007)
The success of Malaysia's development and its administration area result of people's solidarity which has always been preserved and nurtured, Yang di Pertuan Agong Tuanku Mizan zainal Abidin said.